2019
DOI: 10.1002/suco.201800271
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive approach to evaluation of mechanical properties of waste aggregate concrete reinforced by steel fiber

Abstract: Waste aggregate concretes are playing a more and more important role in construction industry. Over the last decade, their application has evolved from very basic pavements and elements with limited mechanical characteristics to full scale structures and large pre‐cast beams and slabs. In some cases, steel fiber was used as the only reinforcement of such elements. The application of steel fiber was based on the assumption that the influence of dispersed reinforcement would be the same as it was in ordinary con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…The conducted research confirmed the possibility of using ceramic sanitary waste in the form of fine and coarse aggregate for the production of concrete composites 14 . Furthermore, other studies have shown that although sanitary ceramics and ceramic kitchen utensils improve the mechanical parameters of concrete, waste brick ceramics not always positively affect its strength 15–17 …”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…The conducted research confirmed the possibility of using ceramic sanitary waste in the form of fine and coarse aggregate for the production of concrete composites 14 . Furthermore, other studies have shown that although sanitary ceramics and ceramic kitchen utensils improve the mechanical parameters of concrete, waste brick ceramics not always positively affect its strength 15–17 …”
Section: Introductionsupporting
confidence: 58%
“…Both ceramic aggregates were planned to be added to mixes in amounts of 20%, 30%, and 40%. These amounts were chosen based on previous authors' experiences with similar waste ceramic aggregates 4,5,17,19 . Nevertheless, the mix with 40% of microfiller (P40) was dismissed due to stiff consistency, which could not be tested using the slump test.…”
Section: Materials and Specimen Preparationmentioning
confidence: 99%
“…Promising results have been obtained as regards the vibration damping coefficient in concrete composites modified by polymers and kinescope glass [45]. In [50][51][52], concrete samples containing different proportions of sand and waste red ceramic aggregate (RWCA) were tested. Among other things, compression and bending samples were tested, crack resistance and fatigue properties were determined.…”
Section: Introductionmentioning
confidence: 99%
“…All ingredients were mixed for 90 s. Ceramic fillers were utilized to partially substitute for the aggregate. Taking into account the previous experience of the research team with similar waste materials [ 19 , 22 , 23 , 24 ], we decided to substitute 10% (by weight) of the aggregate with ceramic fillers. The density of the natural aggregate, ceramic pots, ceramic tiles, and sanitary ceramics was equal to 2.61, 2.40, 2.65, and 2.52 kg/dm 3 , respectively.…”
Section: Research Programmentioning
confidence: 99%